2018 44th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2018
DOI: 10.1109/seaa.2018.00030
|View full text |Cite
|
Sign up to set email alerts
|

Towards Modeling Patterns for Embedded Software Industry: Feedback from the Field

Abstract: The analysis, design, implementation and testing of software for embedded systems are not trivial. Software modeling is a commonly used approach in the embedded software industry to manage complexity of these phases. The modeling approaches vary since the characteristics of modeling such as its purpose, the medium type used, the lifecycle phase used, differ among systems and industrial sectors. Our previous research identified and defined the modeling approach patterns in embedded software development projects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 12 publications
(52 reference statements)
3
10
0
Order By: Relevance
“…As observed in [18], UML is not so popular for prescriptive modeling since its semantics is not exactly defined and this would hamper the automatic translation towards other models. We also found that in model-driven approaches, it is not so important to have a graphical syntax to represent the model (as in UML), but these models should be represented in a format that is readable by a machine (as in DSL) [66]. This also supports our findings on "DSL"s.…”
Section: Modeling Languages (Q14)supporting
confidence: 86%
See 3 more Smart Citations
“…As observed in [18], UML is not so popular for prescriptive modeling since its semantics is not exactly defined and this would hamper the automatic translation towards other models. We also found that in model-driven approaches, it is not so important to have a graphical syntax to represent the model (as in UML), but these models should be represented in a format that is readable by a machine (as in DSL) [66]. This also supports our findings on "DSL"s.…”
Section: Modeling Languages (Q14)supporting
confidence: 86%
“…Then, we focused to fill one major part of the gap in the existing literature by identifying and defining modeling approach patterns in embedded software industry. In order to improve what we found out from this survey result (e.g., quantitative data), we conducted a series of semi-structured interviews over eight months with 53 embedded software professionals to get more personalized, qualitative data [66]. Based on these findings, we created a characterization model, which identifies and defines a modeling stakeholder's pattern and culture as commonsense practices by presenting what the similar profiles is doing while modeling (via the database constructed with survey data presented in this study) [78].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, there was a need to validate and improve this preliminary version. As a second step, we improved these quantitative results with a deeper and more qualitative strategy via in-depth interviewing over eight months with 53 embedded software professionals across a variety of target industrial sectors and roles [10]. As a result, the set of patterns were extended to 12 patterns, where the final set is given in Table 1 [10].…”
Section: Overview Of the Characterization Modelmentioning
confidence: 99%